Keselamatan Dan Kesehatan Kerja Melalui Pendekatan Job Safety Analysis - Habib Nor Rais; Shio Piaggio Orbitan Pasca Wijaya; Shofiyyur Rahman; Rama Erdiyanto; Denny Oktavina Radianto (Lembaga Pengembangan Kinerja Dosen, 2024)
Occupational Safety and Health (K3) is a field that is involved in the safety, health and welfare of people who work in a project or institution. The ultimate goal of implementing Occupational Safety and Health is to maintain safety and health in the work environment. Occupational Safety and Health (K3) practices are carried out with several efforts, including prevention, providing sanctions and compensation, wound healing and care for workers, as well as providing health care and sick leave to workers. Even though the government has issued requirements and regulations governing the protection of workers, in reality the implementation of work or a project still involves neglect of requirements and regulations related to Occupational Safety and Health (K3) due to the lack of awareness of project implementers regarding the magnitude of the risks that must be borne by workers and companies. naturally. It is hoped that updating work procedures will provide warnings as well as new work habits so that previous incidents do not happen again. Activities like this must also be carried out periodically and consistently by continuing to develop monitoring and supervising work implementation methods that are based on an appropriate Occupational Safety and Health system.